Dividend policy, CEO Narcissism, and its influence on companies in Indonesia: A Behavioral Theory of the Firm approach - Vera Oktari; Wiwiek Dianawati (Cogent Economics & Finance, 2023)
In the concept put forward by the Behavioral Theory of the Firm (BTF), the policies implemented must provide added value to the company. In their preparation, policies will be heavily influenced by decision-makers behavior. This study was conducted to see the company's value dividend policy and the impact of CEO Narcissism in that policy. This empirical research involved companies indexed by Kompas 100 from 2011 to 2019 and was tested using Moderated Regression Analysis (MRA). This study confirms that dividend policy is a signal for increasing firm value, so this policy deserves further attention from management. CEO Narcissism drives the increased value generated by the dividend policy and acts as pure moderation. This result is also strengthened by the robustness test conducted on Tobin's Q to measure firm value. This research is the first study to examine the moderating effect of CEO Narcissism on dividend policy and its impact on firm value. Through the findings of this research, it is hoped that this study will contribute to the Behavioral Theory of the Firm and become a guide for companies to pay attention to the dividend policy formulation process so that it provides value, both for shareholders and for the company.
Keywords: 330; behavior; CEO characteristic; CEO Narcissism; dividend policy; firm value; strategy